Conceptual change: a glance from the theories of Piaget and Vygotsky - Raynaudo, Gabriela (2017)
A central issue in contemporary psychology consists in understanding how we develop new cognitive structures and how we modify them. This article aims to address the links between the notions from conceptual change and some aspects from the theories of Piaget and Vygotsky. For that purpose, the notions of implicit theory and scientific concept were analyzed from the theory of conceptual change, and the notions of error and pseudo-concept from the theories of Piaget and Vygotsky. First, we examined the work of representative authors of conceptual change to understand the place granted to the notions of implicit theory and scientific concept. Then, some aspects from the theories of Piaget and Vygotsky were considered to reflect on the place that the notions of error and pseudo-concept have in those theories. Finally, we analyzed and discussed the similarities between the theories of conceptual change, Piaget and Vygotsky. DOI: https://doi.org/10.24265/liberabit.2017.v23n1.10